Prevalence and Impact of Minority Variant Drug Resistance Mutations in Primary HIV-1 Infection - Stekler, Joanne D.; Ellis, Giovanina M.; Carlsson, Jacquelyn; Eilers, Braiden; Holte, Sarah; Maenza, Janine; Stevens, Claire E.; Collier, Ann C.; Frenkel, Lisa M. (PloS one, 2011)
To evaluate minority variant drug resistance mutations detected by the oligonucleotide ligation assay (OLA) but not consensus sequencing among subjects with primary HIV-1 infection. Observational, longitudinal cohort study. Consensus sequencing and OLA were performed on the first available specimens from 99 subjects enrolled after 1996. Survival analyses, adjusted for HIV-1 RNA levels at the start of antiretroviral (ARV) therapy, evaluated the time to virologic suppression (HIV-1 RNA<50 copies/mL) among subjects with minority variants conferring intermediate or high-level resistance. Consensus sequencing and OLA detected resistance mutations in 5% and 27% of subjects, respectively, in specimens obtained a median of 30 days after infection. Median time to virologic suppression was 110 (IQR 62-147) days for 63 treated subjects without detectable mutations, 84 (IQR 56-109) days for ten subjects with minority variant mutations treated with ≥3 active ARVs, and 104 (IQR 60-162) days for nine subjects with minority variant mutations treated with <3 active ARVs (p = .9). Compared to subjects without mutations, time to virologic suppression was similar for subjects with minority variant mutations treated with ≥3 active ARVs (aHR 1.2, 95% CI 0.6-2.4, p = .6) and subjects with minority variant mutations treated with <3 active ARVs (aHR 1.0, 95% CI 0.4-2.4, p = .9). Two subjects with drug resistance and two subjects without detectable resistance experienced virologic failure. Consensus sequencing significantly underestimated the prevalence of drug resistance mutations in ARV-naïve subjects with primary HIV-1 infection. Minority variants were not associated with impaired ARV response, possibly due to the small sample size. It is also possible that, with highly-potent ARVs, minority variant mutations may be relevant only at certain critical codons.